Roles of vaginal flora in human papillomavirus infection, virus persistence and clearance - Zeng, Mi; Li, Xin; Jiao, Xiaoyang; Cai, Xiaochun; Yao, Fen; Xu, Shaomin; Huang, Xiaoshan; Zhang, Qiaoxin; Chen, Jianqiang (Frontiers in Cellular and Infection Microbiology, 2023)
Vaginal flora plays a crucial role in human papillomavirus (HPV) infection and progression to cancer. To reveal a role of the vaginal flora in HPV persistence and clearance, 90 patients with HPV infection and 45 healthy individuals were enrolled in this study and their vaginal flora were analyzed. Women with HPV infection were treated with Lactobacillus in the vaginal environment as a supplement to interferon therapy. Our results indicated that patients with high risk HPV (Hr-HPV) 16/18 infection had a significantly higher alpha diversity compared with the healthy control (p < 0.01), while there was no significant difference between the non-Hr-HPV16/18 group and the controls (p > 0.05). Patients with multiple HPV infection had insignificantly higher alpha diversity compared with single HPV infection (p > 0.05). There were no significant differences in microbial composition among the three groups based on beta diversity. The vaginal flora of patients with HPV infection exhibited different compositions when compared to the healthy controls. The dominant bacteria with the highest prevalence in HPV-positive group were Lactobacillus iners (n = 49, 54.44%), and the top 3 dominant bacteria in the HPV-persistent group were Lactobacillus iners (n = 34, 53.13%), Sneathia amnii (n = 9, 14.06%), and Lactobacillus delbrueckii (n = 3, 4.69%). Patients with HPV clearance had significantly lower alpha diversity, and the flora pattern was also different between groups displaying HPV clearance vs. persistence. The patients with persistent HPV infection had significantly higher levels of Bacteroidaceae, Erysipelotrichaceae, Helicobacteraceae, Neisseriaceae, Streptococcaceae (family level), and Fusobacterium, Bacteroides, Neisseria, and Helicobacter (genus level) than patients who had cleared HPV (p < 0.05). Our study revealed differences in vaginal flora patterns are associated with HPV persistence and its clearance. Interferon plus probiotics can greatly improve virus clearance in some patients. Distinguishing bacterial features associated with HPV clearance in patients would be helpful for early intervention and reverse persistent infection.